Pengaruh PLP II dan Prestasi Belajar Terhadap Minat Menjadi Guru Pada Mahasiswa Pendidikan Ekonomi FKIP Universitas Palangka Raya - Tanti Girsang; Alexandro, Rinto; Sundari, Sundari; Eriawaty, Eriawaty (Edunomics Journal, 2024)
This research uses quantitative research methods. The population is all economic education students and the sample in this research is economic education students class of 2020, FKIP, Palangka Raya University, totaling 37 respondents. The sampling technique uses total sampling. Data collection techniques are through observation, documentation and questionnaires and analyzed using multiple linear regression tests and hypothesis testing through the F test and t test which are processed using the SPSS 25 for Windows application. Based on the results of data analysis using the multiple linear regression equation, the value Y =49,293+ 0,765X1+1,996X2. And the magnitude of the influence of the two independent variables is 46,8%, so 53.2% is influenced by other independent variables that have not been studied by researchers